Fabrication of a multilayer bioabsorbable composite vascular stent utilizing oxidized starch-Fe3O4 nanoparticles and polycaprolactone nanofibers - Fatemeh Hataminia; Reza Faridi-Majidi; Seyed Mohammad Amin Hashemi; Hossein Ghanbari (Scientific Reports)
Abstract Currently, bioabsorbable polymer stents are utilized to mitigate the risk of late stent restenosis in cardiovascular applications. In this context, we propose a novel assembly that integrates polycaprolactone (PCL) nano-fibers and oxidized starch (OS) with iron oxide nanoparticles (IONPs) to create a rigid-swelling scaffold for cardiovascular stents. This study fabricates the nanocomposite (NC) using a combination of electrospinning and electrospray techniques. The stent body is formed by leveraging the self-adhesive (SA) properties of multiple NC sheets, resulting in a multilayer (ML) structure. To achieve the desired stent shape, we employed the CO2 laser cutting method on a specific pattern after rolling the prepared sheets in two steps: OS hydration followed by melting the polymer between layers during the cutting process. Our results show that the multilayer structure of the cardiovascular stent body demonstrates favorable in vitro mechanical properties and biocompatibility.